2019
DOI: 10.11648/j.ijema.20190703.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Anthropogenic Effluents Impacts on the Water Quality Using Principal Component Analysis: A Case Study of Abu-Qir Bay-Alexandria-Egypt

Abstract: Background: The growing increase in Egyptian population, as well as urbanization expansion; lead to a corresponding increase in industrial, agriculture, urban effluents that discharged into the aquatic environment of Egypt. Objective: This study was conducted to evaluate the alteration occurred in some water quality characteristics of different water bodies subjected to different types of pollutants. Methods: Different physicochemical parameters, nutrient salts, total dissolved copper, and total dissolved carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…2(b-f). The present results are in agreement with those of the previous studies (Shaltout et al, 2014;Shreadah et al, 2014;Abdel-Halim et al, 2016;Shreadah et al, 2019).…”
Section: Hydrographical Parameterssupporting
confidence: 94%
See 1 more Smart Citation
“…2(b-f). The present results are in agreement with those of the previous studies (Shaltout et al, 2014;Shreadah et al, 2014;Abdel-Halim et al, 2016;Shreadah et al, 2019).…”
Section: Hydrographical Parameterssupporting
confidence: 94%
“…The present study results (Table 3) revealed that, the overall average values of pH at all sectors are slightly higher than those measured at Abu-Qir Bay sector (Shreadah et al, 2019). Higher pH values suggest that carbon dioxide, carbonate-bicarbonate equilibrium is more affected due to changes in physicochemical condition (Karanth, 1987).…”
Section: Hydrographical Parametersmentioning
confidence: 52%
“…As a matter of fact, they produce a broad variety of unique potent substances, which include among others, carotenoids, terpenoids, xanthophylls, chlorophylls, phycobilins, polyunsaturated fatty acids, polysaccharides, vitamins etc. exhibiting potential beneficial use and stable properties for therapeutic use with low potential toxicity including antioxidant, anti-inflammatory, antiallergenic, antiaging and antiwrinkling effects and ultraviolet protection [ 5 , 6 , 25–28 ]. Moreover, the high level of minerals, vitamins, essential amino acids, indigestible carbohydrates and polyphenols, as well as their bioactive metabolites in the red algae and their relatively easy cultivation makes them attractive [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Alexandrian coast is highly vulnerable to beach erosion, sea-level rise, rip currents, and anthropogenic activities (Soliman et al 2014;Masria et al 2015). The Egyptian Environmental Affairs Agency (EEAA 2015) declares two marine pollution hotspots, Abo-Qir Bay and El-Mex Bay, along the northern coast of Egypt due to their receiving mixtures of variable pollutants (Shreadah et al 2014(Shreadah et al , 2019. In these bays, the high levels of chlorinated organic compounds, hydrocarbon oil, and heavy metal pollution can be found (Khairy et al 2012;El Nemr et al 2013).…”
Section: Introductionmentioning
confidence: 99%